The Role of Gampong Officials in the Implementation of Financial Aid Program of Peumakmu Gampong (A Study in Gampong Pasi Rawa, Sigli City Sub-district, Pidie Regency) - Ismail (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Gampong development is an integral part of national development, because gampong is the basis of every national development as a whole, based on the principle of development that was born from the community, planned by the community, implemented and supervised by the community with the aim for the benefit of the community, then the development is more felt of benefits and its meanings. In the implementation of a gampong-based development program, it is very necessary to have a role for gampong officials in implementing it. The development implement with the role of the gampong officials through the Implementation of Financial Aid Program of Peumakmu Gampong in Pasi Rawa, Sigli City Sub-district, Pidie Regency was run well, because from the beginning the gampong officials had adopted community ideas and accommodated them as outlined in the development program. The implementation is also in accordance with applicable procedures as stipulated by the Aceh Provincial Government as the party providing financial aid. The purpose of this research is of course to describe the implementation process of financial aid program of peumakmu gampong, and to analyze the role of gampong officials in the implementation of that program in Pasi Rawa, Sigli City Sub-district, Pidie District. For this reason, the method used in this study is a qualitative method, because it is believed to be able to get representative results. While the data collection techniques that researchers do through observation, interviews and documentation. The results showed that the Implementation Process of financial aid program of peumakmu gampong in Pasi Rawa Gampong, Sigli City Sub-district has been running well and in accordance with the hopes and desires of community members, even though the implementation did not involve women, and was in line with the objectives and implementation instructions. Then with the role of the gampong officials both in the form of mind and in the form of energy provided without expecting financial rewards, it turns out that it can support the programs that are on target, on time, and also on quality, so as to provide convenience in its implementation. These results have positive implications both for the process and for the results of implementing the financial aid program of peumakmu gampong.